Financial management and financial-related conflict management of newly married couples - Villanueva, June Anne Nathalie C.; Chua, Consuelo trio. (2008.)
This study describes the financial-related conflict and conflict management practices of newly married couples. It also looks at the strategies that couples in their financial resources management and their differences in financial management. Nineteen (19) married couples of eight months to five years participated in the study. In-depth interviews with husbands and wives were conducted to gather information about their financial management strategies, the types of an reasons for their financial-related conflicts and their conflict management practices. Results show the basic financial management strategies used by the newly married couples are budgeting, saving and investing. couples also differ in the ways they allocate their budget, handle their savings, and invest their financial resources. Wives prioritize everyday household needs in their budgets while husbands give more importance to long-term investments. Furthermore, wives save more regularly than their husbands do. Husbands are also more willing to take risks when investing their money. The main reason for financial-related conflicts is improper allocation of money. Other reasons include concealed financial decisions and wastage. Regarding financial-related conflict management, the most common method is the use of preventive measures such as setting rules and goals. Other conflict management strategies used include accommodating, show of affection and side-stepping. Generally, financial management strategies of newly married couples are influenced by their values, experiences, and family backgrounds. Differences in budgeting, saving, and investing are also influenced by these factors. Recommendations for future research are presented at the end of the paper.
Thesis (BS Home Economics)--University of the Philippines Diliman.
Keywords: Newlyweds -- Finance, Personal